Evaluation of Consolidation of Holdings Programme - Case Studies of Maharashtra, Punjab and Haryana, and Uttar Pradesh - Planning Commission (Planning Commission, 1970)
An Assistant Consolidation Officer has a staff consisting of 6 surveyors, 1 Circle Inspector, Nimlandar, 3 Copying Clerks and 1 Junior Clerk. But the staff is not adequate to meet the load of work and to fully implement the targets allotted.
Programme Evaluation Organisation Planning Commission
Programme Evaluation Organisation Planning Commission Government of India